OTOMATISASI PENERANGAN PADA GEDUNG PERKANTORAN BERBASIS PERSONAL KOMPUTER MENGGUNAKAN BAHASA PEMROGRAMAN DELPHI - Al-Mubarok, Noor Husni; Selo, - (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2010)
One of Scientific and Technological product that very fenomenal is computer (personal computer).Personal Computer (PC) gives various facilities for the amenity of user whether as machine of numerator oras sophisticated data processor.Technological Affiliation of computer with the electricity, can produce the masterpiece of LightningAutomatition at Officeblock, that writer chooses as his research skripsi theme. PC with the Ianguage ofDelphi programming will give the controller system centrally and scheduled as according to office hours.Interface of system of Lightning Automatization at this Officeblock uses the PPI (ProgrammablePeripheral Interface) 8255 the operation uses Mode 0. Delphi will control the system of through interface PPI8255. In this research, the operational of PPI 8255 uses Mode 0 as determinant of port I/O for the enkindlingof ace. PB0-7 and PC4-7 as port output will turn the lightning on based on the confirmation of port input andsetting in each date of room. Port input port is PA0-7 and PC0-3 as censor simulation which can be activatedand deactivated from central. moment of censor simulation is being activated, it will work to recognize onewho enter the column after office hours in strarted. Moment of censor Simulation is being deactivated thehence enkindling of column lighting only based on the setting in each, date of to column. Setting in each,date of can fillup the duration of time of lamp enkindling that is hour, minute and second from the light is onuntil it is off. In input every date of data can be done in one time to control one week, one month and so on,so the system of Lightning Automatition at this officeblock will economize the time and energy of theenkindling operator / lamp extinction.Keyword: Personal Computer, Programmable Peripheral Interface, Lamp.